The role of proteases in regulating Eph/ephrin signaling - Atapattu, Lakmali (Cell Adh Migr, 2014)
Proteases regulate a myriad of cell functions, both in normal and disease states. In addition to protein turnover, they regulate a range of signaling processes, including those mediated by Eph receptors and their ephrin ligands. A variety of proteases is reported to directly cleave Ephs and/or ephrins under different conditions, to promote receptor and/or ligand shedding, and regulate receptor/ligand internalisation and signaling. They also cleave other adhesion proteins in response to Eph-ephrin interactions, to indirectly facilitate Eph-mediated functions. Proteases thus contribute to Eph/ephrin mediated changes in cell-cell and cell-matrix interactions, in cell morphology and in cell migration and invasion, in a manner which appears to be tightly regulated by, and co-ordinated with, Eph signaling. This review summarizes the current literature describing the function and regulation of protease activities during Eph/ephrin-mediated cell signaling.